A atuação dos atores no processo de formação da agenda de inclusão financeira no Brasil - Sela, Vilma Meurer (2017)
This thesis aimed to analyze the actors performance in Financial Inclusion agendasetting process in Brazil, focusing on analysis of (1) how actors articulated themselves in defense of their ideas and interests in conclusive process of a public policy, and (2) what non-human elements influenced the agenda-setting process. Actor-Network Theory was used as a theoretical lens, since it is understood that the agenda-setting can be taken through a continuous process of associations between different mediators called actants (human and non-human). The research was guided by qualitative research procedures, it used primary data (semi-structured interviews) and secondary data (laws, decrees, regulations, reports, minutes of Financial Inclusion Forums, and others). Interviews were carried out with 19 participants using snowball technique, between October and December 2016. Data were tested through content analysis using Atlas TI Software. The agenda of Financial Inclusion in Brazil is the result of an incremental process, which was attended by a wide range of actors (government, market, developers and scholars and international actors) that was influenced by some non-human elements (macro-actors). The dynamics of Financial Inclusion agenda-setting process in Brazil was analyzed through four phases of translation, presented by Callon (1986). During these four phases, it was possible: (problematization) to identify the identity of the actors who acted in Financial Inclusion agenda-setting process, in which the BCB is the focal actor of this process, as well as the Obligatory Passage Point (OPP), that was the union of efforts searching for solutions to the exclusion of low income population; (interessement) to emphasize the articulation process of network relations for financial inclusion, originated from First Financial Inclusion Forum; (enrolment) to emphasize cooperation among actors, which aimed to catalyze efforts towards a common goal, and searched to play their roles, within their abilities; and (mobilization) to show actors efforts as representative entities of public interest.